A Numerical Study of The Heat Transfer Intensification Using High Amplitude Acoustic Waves - RULIK, Sebastian; WRÓBLEWSKI, Włodzimierz (Archives of Acoustics, 2018)
The current practice in the efforts aiming to improve cooling conditions is to place emphasis on the application of non-stationary flow effects, such as the unsteady jet heat transfer or the heat transfer intensification by means of a high-amplitude oscillatory motion. The research presented in this paper follows this direction.A new concept is put forward to intensify the heat transfer in the cooling channels with the use of an acoustic wave generator. The acoustic wave is generated by a properly shaped fixed cavity or group of cavities.The sound generated by the cavity is a phenomenon analysed in various publications focused on the methods of its reduction. The phenomenon is related to the feedback mechanism between the vortices flowing from the leading edge and the acoustic waves generated within the cavity. The acoustic waves are generated by the interaction between the vortices and the cavity walls. Strong instabilities can be observed within a certain range of the free flow velocities. The investigations presented in this paper are oriented towards the use of the phenomenon for the purposes of the heat transfer process intensification. The first part of the work presents the numerical model used in the analysis, as well as its validation and comparison with empirical relations. The numerical model is constructed using the commercial CFDAnsys CFX-16.0 commercial program.The next part includes determining of the relationship between the amplitude of the acoustic oscillations and the cooling conditions within the cavity. The calculations are performed for various flow conditions.